Sepsis Diagnostic Methods and Protocols - Mancini, Nicasio.; Mancini, Nicasio. (Methods in Molecular Biology,, 2015)
This volume covers microbiological, clinical and patophysiological aspects of sepsis and also provides general overview chapters with every chapter discussing the real clinical impact of the discussed diagnostic approaches. Sepsis is a major clinical problem that takes an inordinate toll on human lives and economical resources. It is widely recognized that inappropriate treatment is associated with a dramatic  increase in mortality, especially within the first hours, therefore clinical and microbiological diagnosis are of pivotal importance in the management of septic patients. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Sepsis: Diagnostic Methods and Protocols seeks to serve both professionals and novices with its well-honed methodologies in an effort to further our knowledge of this life-threatening illness.